Synthesis and optical properties of Dy~（3＋）, Li~＋ doped CaMoO_4 phosphor - 关丽 贾国奇 杨保柱 李旭 金立涛 杨志平 傅广生 (Journal of rare earths, 2011)
A series of CaMoO4 phosphors doped with trivalent dysprosium ions （Dy3＋） and lithium （Li＋） were prepared by solid state method at 750 °C for 3 h. X-ray diffraction （XRD） confirmed the crystal structure and quality of phosphors. Scanning electron microscopy （SEM） in- dicated that the phosphors presented good crystalline state, and the crystalline grain sizes were about 0.5–3.0 μm. The emission spectra showed that the phosphors had intense emission at 480 （4F9/2→6H15/2）, 576 （4F9/2→6H13/2） and 660 nm （4F9/2→6H11/2）. Meanwhile, the excited spectra indicated it had intense excitation at 352 （6H15/2→6P7/2）, 390 （6H15/2→4M21/2） and 450 nm （6H15/2→4I15/2）. As a charge compensator, Li＋ ions were incorporated into CaMoO4：Dy3＋ phosphors, which enhanced the PL intensities depending on the doping concentration of Li＋. The optimal molar fraction of Dy3＋ ions in Ca1-xMoO4：xDy3＋, 0.05Li＋ was 0.05.